Noise Induced Hearing Loss (NIHL):An Emerging Health Hazard Among Urban Children (Central Medical College Journal, 2022)
Background: Noise has been recognized for hundreds of years as hazardous to health. In big cities, the children are more prone to Noise Induced Hearing Loss (NIHL) due to high frequency sounds from different sources. Early reliable diagnosis of hearing loss is essential to adopt appropriate treatment to minimize potential developmental delays attributed to loss. This corner of child health hazards is less addressed ever before in our country.Methodology: This study was designed as a cross sectional, observational study conducted in Chittagong metropolitan city of Chittagong district under the guidance of the Department of Physiology, Chattogram Medical College, Chattogram. The study was conducted among the children of 5 to 18 years of age. Sample size was 500. Study was conducted over 1 year of period from November 2009 to October 2010. Hearing status of all children were tested by pure tone audiometry at 250, 500, 1000, 2000, 4000 and 8000 Hz using sound intensity ranging from 0 – 120 dB.Result: 268 (53.6%) samples were male and 232 (46.4%) were female. The average sound level of study area were 90dB (highest) and 60 dB (lowest) at peak hour. This was evident that Mild degree of NIHL was quite high in the study area (8%) and total affected children were 9.2%. Male (7.6%) children are more affected by NIHL than female (2.39%) children. Maximum respondents are affected bilaterally (89.13%).Conclusion: Prevalence of NIHL was remarkably high in urban areas among children. All efforts of public health interventions such as education, training, audiometric testing, exposure assessment, hearing protection, noise control and community based awareness programme when feasible should be targeted to prevent the NIHL from childhood and to achieve the best hearing conservation of general population.Central Medical College Journal Vol 5 No 1 Jan 2021 PP 7-12